2019
DOI: 10.14202/vetworld.2019.1108-1115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of NS5B gene from bovine viral diarrhea virus-infected cattle in Central and East Java, Indonesia

Abstract: Background and Aim: A previous study divided Indonesian bovine viral diarrhea virus (BVDV)-1 into subgenotypes BVDV-1a to BVDV-1d based on the partial NS5B gene using strain Bega as reference for BVDV-1a. In fact, it is clustered into BVDV-1c with strain Bega-like Australia. BVDV genotyping has been done on isolates from Jakarta, West and Central Java, but East Java isolates have not been genotyped. This study aimed to analyze genetic variability and amino acid residues in the nucleotide-binding pocket of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The prevalence of the disease continues to increase over the years. The seropositivity of BVDV-1 among beef, dairy, and breeding cattle populations varies from approximately 46-56.2% [ 15 , 16 ]. Because BVDV-1 from cattle is the only officially recognized pestivirus species in Indonesia, all studies related to this virus are focused on cattle as the natural host and no research on pestiviruses in small ruminants has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the disease continues to increase over the years. The seropositivity of BVDV-1 among beef, dairy, and breeding cattle populations varies from approximately 46-56.2% [ 15 , 16 ]. Because BVDV-1 from cattle is the only officially recognized pestivirus species in Indonesia, all studies related to this virus are focused on cattle as the natural host and no research on pestiviruses in small ruminants has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from culture-and protein-based tests, RNA-based tests have also been widely used to detect and characterise Indonesian isolates of BVDV, especially for genotyping [44][45][46]48,49].…”
Section: Isolation and Detectionmentioning
confidence: 99%
“…Studies of BVDV subgenotypes in Indonesia mainly used genes NS5B or 5 UTR for analyses, but genes Npro, NS3 and E2 were also used. A study of a 360-nucleotide fragment of the NS5B gene of BVDV indicated that subgenotypes-1a, -1b and -1c were circulating in the Banyumas region, Central Java, during 2013-2016 [45]. The sequences used in this study are accessible in GenBank with the accession numbers MK411754, MK411755, MK411756, MK411757, MK411762, MK411764, MK411765, MK411761 and MK411759 for BVDV-1a, MK 411760 for BVDV-1b and MK411751, MK411763, MK411753, MK411758 and MK411752 for the BVDC-1c genotypes.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that there are two main BVDV1 subgenotypes, 1a and 1c (Saepulloh et al 2015; Wuryastuti et al 2015, in addition to other subgenotypes, 1b and 1d (Saepulloh et al 2015). The distribution of three subgenotypes, namely, BVDV 1a, 1b, and 1c, in Central and East Java, Indonesia, re flects the genetic variability of BVDV1 viruses based on partial NS5B genes (Irianingsih et al 2019). Phylogenetic analysis from different regions, specifically 5′ NCR, Npro, E2, NS3, and NS5B3' NCR, of BVDV isolates has been carried out in Japan (Nagai et al 2004) and 5'UTR nd NPro in the UK (Booth et al 2013).…”
Section: Introductionmentioning
confidence: 99%